Skills Gap: The Importance of Soft Skills in Graduate Employability as Perceived by Employers and Graduates - Yong, Brenda Ping Ping; Ling, Ying-Leh (Online Journal for TVET Practitioners, 2023)
This study investigated the perceptions of soft skills among employers and graduates in Sarawak, using descriptive quantitative research methodology to determine if there is a significant difference between the employers and graduates; to compare differences in ranking of soft skills, and thus the occurrence of a skills gap between both parties. The literature reviews in this study emphasized, firstly, the perceptions of graduates and employers on soft skills about employability, a topic which had been studied over the decades across the world, since the skills gap or mismatch arose from the different perceptions is an ongoing phenomenon, that affected the curriculum of the higher education institutions and the labour market in the industries. Second, soft skills development has evolved; it has been referred to as 21st-century skills; a critical component of today's graduates' employability. Then, this study examined the perception of stakeholders involved in graduate employability, in particular, employer and graduate. The skills gap existed as a result of the disparities in perceptions between graduates and employers as the findings revealed there are differences in ranking orders, and frequency analysis confirmed the mean score comparisons of the ranking options between both parties. In terms of employers’ demographic characteristics, significant differences were spotted after analysing a one-way ANOVA.  These findings aimed to provide useful information to the stakeholders involved in assisting with the reduction of the skills gap and hence improve the graduate employability in Sarawak.